Mapping of a novel clubroot disease resistance locus in Brassica napus and related functional identification - Jiang, Xuefei; Su, Ying; Wang, Maolin (Frontiers in Plant Science, 2022)
Clubroot disease, caused by Plasmodiophora brassicae, is a devastating disease that results in substantial yield loss in Brassicaceae crops worldwide. In this study, we identified a clubroot disease resistance (CR) Brassica napus, “Kc84R,” which was obtained by mutation breeding. Genetic analysis revealed that the CR trait of “Kc84R” was controlled by a single dominant locus. We used the bulked segregant analysis sequencing (BSA-seq) approach, combined with genetic mapping based on single nucleotide polymorphism (SNP) markers to identify CR loci from the F2 population derived from crossing CR “Kc84R” and clubroot susceptible “855S.” The CR locus was mapped to a region between markers BnSNP14198336 and BnSNP14462201 on the A03 chromosome, and this fragment of 267 kb contained 68 annotated candidate genes. Furthermore, we performed the CR relation screening of candidate genes with the model species Arabidopsis. An ERF family transcriptional activator, BnERF034, along with the identification of P. brassicae infection in Arabidopsis homozygous knockout mutants and transgenic lines of BnERF034, was shown to act as a negative regulator in clubroot disease. Additionally, the expression analysis between resistant and susceptible materials indicated that BnERF034 was identified to be the most likely CR candidate for the resistance in Kc84R. To conclude, this study reveals a novel gene responsible for CR. Further analysis of BnERF034 may reveal the molecular mechanisms underlying the CR of plants and provide a theoretical basis for Brassicaceae resistance breeding.